Pre‐operative reference ranges for ROTEM® sigma in patients undergoing cardiac surgery: a secondary analysis of two prospective trial cohorts - Haeren, Maite M. T.; Brouwers, Meike; Schenk, Jimmy; Breel, Jennifer S.; Noteboom, Sijm H.; Kho, Eline; Eberl, Susanne; Veelo, Denise P.; Vlaar, Alexander P. J.; Müller, Marcella C. A.; Hermanns, Henning (Anaesthesia, 2025)
Summary Introduction Rotational thromboelastometry (ROTEM®) is used widely in cardiac surgery. Reference ranges are derived from healthy volunteers but may not be interchangeable with those from patients undergoing cardiac surgery. Furthermore, sex and age seem to influence rotational thromboelastometry profiles. We performed a secondary analysis of two prospective observational study cohorts from a single centre in the Netherlands, which establishes pre‐operative ROTEM® sigma reference ranges for adult patients undergoing cardiac surgery and examines sex‐ and age‐specific variations. Methods Reference ranges (2.5–97.5th percentiles) were compared with those reported by the manufacturer by calculating 95%CIs around the percentiles. Sex‐ and age‐specific variations were evaluated similarly by creating subgroups (comparing males with females and different age groups) and calculating the 95%CIs for the ranges in each subgroup. Non‐overlapping CIs indicated statistically significant different ranges. Results We included 381 patients in the analysis. Differences were found in ROTEM sigma reference ranges compared with those stated by the manufacturer: EXTEM and FIBTEM clot firmness upper limits were higher, and clotting time ranges in EXTEM and INTEM were wider. The lower limit of LI60 EXTEM was lower. When comparing males (n = 260) and females (n = 121), female patients had shorter CT EXTEM and higher A5, A10 and MCF in EXTEM and FIBTEM, but the reference ranges were not significantly different. No differences in medians or reference bounds were found across four age categories, divided by quartiles. Discussion Reference ranges for patients undergoing cardiac surgery differed from the manufacturer reference ranges. Pre‐operatively, female patients exhibited a slightly more hypercoagulable ROTEM profile than males when comparing medians, though the reference ranges were similar. No differences were found across age categories. Cardiovascular‐specific, but not sex‐ or age‐specific ROTEM sigma reference ranges might be needed.